2020
DOI: 10.1111/jar.12841
|View full text |Cite
|
Sign up to set email alerts
|

Group climate, aggressive incidents and coercion in a secure forensic setting for individuals with mild intellectual disability or borderline intellectual functioning: A multilevel study

Abstract: A high number of aggressive incidents in secure forensic care are considered a serious problem, not only for clients but also for sociotherapists 1 as well (Robinson et al., 2018;Ros et al., 2013).According to the results of a study presented by one of the Dutch labour unions (CNV, Zorg & Welzijn, 2018) addressing aggressive incidents in Dutch health care for people with intellectual disabilities, more than 50% of the 640 caregivers experienced physical (70%) or verbal (79%) aggressive incidents in their work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Repression by staff is related to aggressive behaviour in clients with MID‐BIF and represents a major impediment to successful forensic residential treatment (De Valk, 2019; Neimeijer et al, 2021). Therefore, it is necessary to reduce coercive measures such as physical restraint, seclusion and chemical restraint and use less restrictive means to minimise aggressive behaviour and maximise treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repression by staff is related to aggressive behaviour in clients with MID‐BIF and represents a major impediment to successful forensic residential treatment (De Valk, 2019; Neimeijer et al, 2021). Therefore, it is necessary to reduce coercive measures such as physical restraint, seclusion and chemical restraint and use less restrictive means to minimise aggressive behaviour and maximise treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although both group climate quality and dynamic risk factors appear to affect the occurrence of inpatient aggression in clients with MID‐BIF (see e.g. Drieschner et al, 2013; Neimeijer et al, 2021), there is a gap in our understanding of the relations between dynamic risk factors for externalising problem behaviour and group climate quality in this target group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…support, growth, atmosphere and repression) were used to operationalize group climate within this study. Given that group climate is measured by the GCI within this setting (Neimeijer et al, 2019(Neimeijer et al, , 2020, we believe that this is an appropriate choice. Another topic list with regard to group climate might have led to other dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown associations between an open group climate and favourable clinical outcomes in clients without intellectual disabilities, such as greater personal development (Van der Helm, Stams, Van Genabeek, & Van der Laan, 2012), increased empathy (Heynen et al, 2017;Van der Helm, Stams, Van der Stel, et al, 2012), fewer mental problems (Beijersbergen et al, 2014), greater internal locus of control (Van der Helm et al, 2009), adaptive coping skills, higher level of treatment motivation (Van der Helm et al, 2014), less aversive responses to social problem situations such as hostile and aggressive behaviour (Eltink et al, 2015), and less aggressive behaviour (Robinson et al, 2018;Van den Tillaart et al, 2018). An association between an open group climate and less aggressive behaviour has also been found in clients with mild intellectual disabilities (Neimeijer et al, 2021).…”
mentioning
confidence: 96%